Ultrafine Particulate Matter in Methane-Air Premixed Flames With Oxygen Enrichment - Dasappa, Shruthi; Camacho, Joaquin (Frontiers in Mechanical Engineering, 2021)
A complementary computational and experimental study is carried out on the formation of ultrafine particulate matter in premixed laminar methane air flames. Specifically, soot formation is examined in premixed stretch-stabilized flames to observe soot inception and growth at relatively high flame temperatures common to oxygen enriched applications. Particle size distribution functions (PSDF) measured by mobility sizing show clear trends as the equivalence ratio increases from Φ = 2.2 to Φ = 2.4. For a given equivalence ratio, the measured distribution decreases in median mobility particle size as the maximum flame temperature increases from approximately 1950 K to 2050 K. The median mobility particle size is 20 nm or less for all flame conditions studied. The volume fraction decreases with increasing flame temperature for all equivalence ratio conditions. The Φ = 2.2 condition is close to the soot inception limit and both number density and volume fraction decrease monotonically with increasing flame temperature. The higher equivalence ratio conditions show a peak in number density at 2000 K which may indicate competing soot inception processes are optimized at this temperature. Flame structure computations are carried out using detailed gas-phase combustion chemistry of the Appel, Bockhorn, Frenklach (ABF) model to examine the connection of the observed PSDF to soot precursor chemistry. Agreement between measured and computed flame standoff distances indicates that the ABF model could provide a reasonable prediction of the flame temperature and soot precursor formation for the flames currently studied. To the first order, the trends observed in the measured PSDF could be understood in terms of computed trends for the formation of benzene, naphthalene and other soot precursors. Results of the current study inform particulate matter behavior for methane and natural gas combustion applications at elevated temperature and oxygen enriched conditions.